2018
DOI: 10.1002/cncy.22049
|View full text |Cite
|
Sign up to set email alerts
|

Nodular fasciitis of the parotid gland: A challenging diagnosis on FNA

Abstract: BACKGROUND: Nodular fasciitis (NF) is a clonal, self-limited proliferation that has only rarely been described in the parotid gland. Because of its potential to mimic benign and malignant parotid neoplasms clinically, radiographically, and cytomorphologically, NF is often managed with unnecessary surgery, which is associated with a risk for significant surgical complications. The purpose of this study is to present the clinical and cytomorphologic findings for NF of the parotid gland by fine-needle aspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In this study, there were 4 nonneoplastic cases on surgical follow‐up that were diagnosed in the benign neoplasm category, including a benign squamous‐lined cyst, sialadenitis, nodular oncocytic hyperplasia, and nodular fasciitis, the last of which was misclassified because of the predominance of adjacent abnormal‐appearing salivary gland tissue in the FNA material. However, nodular fasciitis is recognized to be a challenging diagnosis on FNA and can mimic primary salivary gland neoplasms in the parotid gland 25,26 . Although there have been a number of studies assessing the performance of the MSRSGC, most of the literature provides data at the category level and does not break down the diagnostic accuracy for specific diagnoses or differentials.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were 4 nonneoplastic cases on surgical follow‐up that were diagnosed in the benign neoplasm category, including a benign squamous‐lined cyst, sialadenitis, nodular oncocytic hyperplasia, and nodular fasciitis, the last of which was misclassified because of the predominance of adjacent abnormal‐appearing salivary gland tissue in the FNA material. However, nodular fasciitis is recognized to be a challenging diagnosis on FNA and can mimic primary salivary gland neoplasms in the parotid gland 25,26 . Although there have been a number of studies assessing the performance of the MSRSGC, most of the literature provides data at the category level and does not break down the diagnostic accuracy for specific diagnoses or differentials.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for tumor growth and metastasis may depend on how tumor cells benefit by reshaping the stroma through different molecular mechanisms. Keloid-like collagen and myxoid stroma are distinct fibrotic stroma features formed by activated CAFs, although these features can also be seen in non-malignant diseases ( 31 , 32 ), such as inflammatory responses to infection and benign tumors. However, the present study found that these features are mainly located in the front of the primary tumor of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nodular fasciitis is a benign proliferating fibroblastic tumour which is most commonly found in the upper arms but can be found in any part of the body including the salivary gland 1. Majority of nodular fasciitis lesions in the salivary gland have been reported to be intraparotid 2. Nodular fasciitis most commonly presents in adults of age 20–50 years 3 4.…”
Section: Discussionmentioning
confidence: 99%